Índices de crescimento e componentes da produção do milho e soja em sistemas agrossilvipastoris - Quintino, Andréia da Cruz (2015)
Agroforestry systems are characterized by the diversification of production comprising several activities and cultures involving agriculture, forestry and cattle-raising activities within the same area and the same system for higher efficiency in land use. Growth indexes and production components of corn and soybean in agroforestry systems were assessed. Two field experiments were undertaken in the area Embrapa Gado de Corte, in Campo Grande MS Brazil (20º27’ S; 54º37’ W; 530 m altitude) during the 2012-2013 agricultural year. Agroforestry system was implemented in January 2009 by transplanting eucalyptus seedlings in simple rows with spacing 14 x 2m and 22 x 2m (East-West). Eucalyptus plants were 4 years old and 21 m high when the annual crops were planted. In December 2012, the first experiment with corn was conducted in 216 m2 plots, and was composed of four paddocks totaling 864 m2 in a 22 x 2m (ILPF22m) agroforestry system; corn was sown at a 0.90 m spacing within the eucalyptus spaces. The second experiment had a total area of 20 ha and was composed of twelve 16.666 m2 paddocks. Soybean was planted in November 2012 in the three integrated systems of agricultural production (ILPF22m: agriculture-livestock-forestry, spacing of eucalyptus 22 x 2 m; ILPF14m: agriculture-livestock-forestry, spacing of eucalyptus 14 x 2 m; ILP: agriculture-livestock). Randomized block design was employed for corn, with four replications, with sub-subdivided split plots. Each split plot (main treatment) comprised three corn hybrids (9005 PRO, 390 PRO and 2B707 HX); sub-split plots (secondary treatment) comprised two cultivation modes of corn crop (corn in monoculture and intercropped with piatã grass); sub-sub split plot comprised the sampling sites A, B, C, D and E (North-South), with distances 3 m, 7 m, 11 m, 7 m and 3 m from tree rows, respectively, with Site C as the central site between the tree rows. At mid-day, corn plants were totally covered under the eucalyptus canopy at distances A and E; covering was intermediate at B and D distance; plants were totally exposed to the sun at C (outside the canopy). Growth indexes, such as relative and absolute growth rates, net assimilation rate and leaf area index of plants in the split plot, were assessed. Number of grains per cob, total mass of grains per cob, mass of 1000 grains, cob yield and grain productivity were the production components of corn evaluated in the central row of the split plot. Growth indexes and production components of corn were affected by the intensity of photosynthetic radiation at the sampling sites close to the eucalyptus rows. Lowest productivity rates of the hybrids under analysis occurred at these sites. The second experiment (soybean) comprised randomized block designs with four replications. Treatments consisted of subdivided split plots. Each plot (main treatment) comprised the three systems of production integration (ILPF22m, ILPF14m, ILP), the sub-split plot (secondary treatment) comprised the five sampling sites of the agroforestry systems with 3 m, 7 m, 11 m, 7 m, 3 m as the distances of the eucalyptus rows for ILPF22m and distances 2.2 m, 4.6 m, 7 m, 4.6 m, 2.2 m for ILPF14m. Sampling sites were identified by A, B, C, D, E (NorthSouth). Soybean cultivar BRS 318RR was used. Photosynthetically active radiation (PAR) was evaluated fortnightly over the soybean canopy. Growth indexes were evaluated taking into account absolute and relative growth, net assimilation rate and leaf area index. Production components of soybean such as grain productivity, amount of pods per plant, mass of one thousand grains and harvest index were evaluated. Corn production components decreased at sampling sites near the eucalyptus canopy due to shade. ILP system provided higher growth and productivity indexes of soybean than ILPF systems. Soybean was more promising under shading. Grain production was higher than corn even with RFA restrictions in certain sampling sites.